Assessment of an Innovative Voluntary Substance Abuse Treatment Program Designed to Replace Compulsory Drug Detention Centers in Malaysia. (28th January 2018) - Khan, Farrah; Krishnan, Archana; Ghani, Mansur A.; Wickersham, Jeffrey A.; Fu, Jeannia J.; Lim, Sin How; Dhaliwal, Sangeeth Kaur; Kamarulzaman, Adeeba; Altice, Frederick L.
ABSTRACT: Background: As part of an ongoing initiative by the Malaysian government to implement alternative approaches to involuntary detention of people who use drugs, the National Anti-Drug Agency has created new voluntary drug treatment programs known as Cure and Care (C&C) Centers that provide free access to addiction treatment services, including methadone maintenance therapy, integrated with social and health services. Objectives:   We evaluated early treatment outcomes and client satisfaction among patients accessing C&C treatment and ancillary services at Malaysia's second C&C Center located in Kota Bharu, Kelantan. Methods: In June-July 2012, a cross-sectional convenience survey of 96 C&C inpatients and outpatients who entered treatment >30 days previously was conducted to assess drug use, criminal justice experience, medical co-morbidities, motivation for seeking treatment, and attitudes towards the C&C. Drug use was compared for the 30-day-period before C&C entry and the 30-day-period before the interview. Results: Self-reported drug use levels decreased significantly among both inpatient and outpatient clients after enrolling in C&C treatment. Higher levels of past drug use, lower levels of social support, and more severe mental health issues were reported by participants who were previously imprisoned. Self-reported satisfaction with C&C treatment services was high. Conclusions/Importance: Preliminary evidence of reduced drug use and high levels of client satisfaction among C&C clients provide support for Malaysia's ongoing transition from compulsory drug detention centers (CDDCs) to these voluntary drug treatment centers. If C&C centers are successful, Malaysia plans to gradually transition away from CDDCs entirely.